The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1074/jbc.m200807200
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Modifying the Surface Charge on the Catalytic Activity of a Thermolysin-like Protease

Abstract: The impact of long range electrostatic interactions on catalysis in the thermolysin-like protease from Bacillus stearothermophilus was studied by analyzing the effects of inserting or removing charges on the protein surface. Various mutations were introduced at six different positions, and double-mutant cycle analysis was used to study the extent to which mutational effects were interdependent. The effects of single point mutations on the k cat /K m were non-additive, even in cases where the point mutations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Each buffer used for characterization of DmbA had a different pH optimum. Evidence for the double pH optimum has been previously reported, for example, with potato invertase (40), 1,2-diacylglycerol kinase of the human erythrocyte membrane (1), UDP-glucose dehydrogenase (39), ATP-dependent DNase (11), and thermolysin-like protease (10). Haloalkane dehalogenases use three ionizable amino acids for their catalysis, but DmbA is currently the only family member showing more than one pH optimum.…”
Section: Discussionmentioning
confidence: 99%
“…Each buffer used for characterization of DmbA had a different pH optimum. Evidence for the double pH optimum has been previously reported, for example, with potato invertase (40), 1,2-diacylglycerol kinase of the human erythrocyte membrane (1), UDP-glucose dehydrogenase (39), ATP-dependent DNase (11), and thermolysin-like protease (10). Haloalkane dehalogenases use three ionizable amino acids for their catalysis, but DmbA is currently the only family member showing more than one pH optimum.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have no data to prove that mutations at 10 Å are at a ''safe'' distance from an enzyme active site. Indeed, experimental studies (de Kreij et al 2002;Rajagopalan et al 2002) have shown that even mutations Figure 4. The average maximum abs(DpK a value) obtainable for all targets as a function of a number of mutations and minimum distance allowed between any atom of the mutated residue and any atom of the target residue.…”
Section: Discussionmentioning
confidence: 99%
“…A literature survey indicated that an alteration of enzyme surface charges via site-directed mutagenesis or chemical modification was an effective way to change the active-site electrostatics, and hence the ionization constants of amino acid residues in the active-site (Afzal et al, 2007;de Kreij et al, 2002;DeSantis and Jones, 1998;Loewenthal et al, 1993). This finding has induced our hypothesis that the ionization constant of catalytic imidazolium may increase, if the hydrolase is immobilized on a hexamethylenamino-activated support (Sepabeads @ EC-HA) to decrease the negative surface charges via multipoint attachments of the carboxylic acid groups to the support.…”
Section: Introductionmentioning
confidence: 96%